The bladder microbiome of NMIBC and MIBC patients revealed by 2bRAD-M - Sun, Jian-Xuan; Xia, Qi-Dong; Zhong, Xing-Yu; Liu, Zheng; Wang, Shao-Gang (Frontiers in cellular and infection microbiology, 2023)
Bladder cancer (BCa) is the most common malignancy of the urinary tract which can be divided into non-muscle-invasive bladder cancer (NMIBC) and muscle-invasive bladder cancer (MIBC), and their microbial differences are not fully understood. This study was conducted by performing 2bRAD sequencing for Microbiome (2bRAD-M) on NMIBC and MIBC tissue samples to investigate the microbiota differences between NMIBC and MIBC individuals. A total of 22 patients with BCa, including 7 NMIBC and 15 MIBC, were recruited. Tumor tissues were surgically removed as samples and DNA was extracted. Type IIB restriction endonucleases were used to enzymatically cleave the microbial genome for each microbe's tag and map it to species-specific 2bRAD markers to enable qualitative and quantitative studies of microbes between MIBC and NMIBC tissues. A total of 527 species were detected. The microbial diversity of NMIBC tissues was significantly higher than that of MIBC tissues. Microbial composition of the two tumor tissues was similar, where Ralstonia_sp000620465 was the most dominant species. 4 species (Acinetobacter_guillouiae, Anoxybacillus_A_rupiensis, Brevibacillus_agri and Staphylococcus_lugdunensis) were enriched in NMIBC, while Ralstonia_mannitolilytica, Ralstonia_pickettii, and Ralstonia_sp000620465 were overrepresented in MIBC. 252 discriminatory character taxa were also revealed by linear discriminant analysis effect sizea (LEfSe). Species importance point plots identified Ralstonia_sp000620465, Cutibacterium_acnes and Ralstonia_pickettii as the three most important species between the two groups. Meanwhile, functional annotation analysis showed 3011 different COGs and 344 related signaling pathways between MIBC and NMIBC microbiome. This first 2bRAD-M microbiome study on MIBC and NMIBC tissues revealed significant differences in the microbial environment between the two groups, which implies a potential association between tumor microbial dysbiosis and BCa, and provides a possible target and basis for subsequent studies on the mechanisms of BCa development and progression.